Physico-chemical and cytotoxic properties of capsules of nanodiamonds/extract of Mimosa Tenuiflora bark with chitosan in MDA-MB-231 - Martel-Estrada, Santos-Adriana (2021)
Cancer research is currently a biomedical concern as its worldwide incidence is estimated to be around 20 million by 2025. In this work, the synthesis of a composite of nanodiamonds/arabinogalactans of Mimosa Tenuiflora bark with chitosan is described. The morphology and physicochemical characterisation of the composites were conducted using Fourier transform infrared (FTIR), scanning electron microscopy (SEM) microscopy, thermogravimetric analysis (TGA), and X-ray diffraction. The cytotoxicity of the composites to breast cancer cells was evaluated. FTIR spectrum demonstrated the chemical interaction between the components, as visible in the TGA. The result suggests that chitosan predominates on the nanodiamond surface through a chemical immobilisation test by solubility and X-ray diffraction analysis. The concentration of 50 μg/mL of nanocapsules shows that almost 60% of cancer cells were killed after 24 h of incubation. This action is specifically against cancer cells. These results indicate that this composition is promising for the treatment of breast cancer.